2015
DOI: 10.1186/s13750-015-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

Are alternative livelihood projects effective at reducing local threats to specified elements of biodiversity and/or improving or maintaining the conservation status of those elements?

Abstract: Background: Alternative livelihood projects are used by a variety of organisations as a tool for achieving biodiversity conservation. However, despite characterising many conservation approaches, very little is known about what impacts (if any) alternative livelihood projects have had on biodiversity conservation, as well as what determines the relative success or failure of these interventions. Reflecting this concern, Motion 145 was passed at the Vth IUCN World Conservation Congress in 2012 calling for a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 26 publications
0
102
0
5
Order By: Relevance
“…Such alternative‐livelihood interventions are focused on reducing livelihood dependency on wildlife (also known as decoupling) (Roe et al. ; Wright et al. ).…”
Section: Developing a Toc For Combatting Iwtmentioning
confidence: 99%
“…Such alternative‐livelihood interventions are focused on reducing livelihood dependency on wildlife (also known as decoupling) (Roe et al. ; Wright et al. ).…”
Section: Developing a Toc For Combatting Iwtmentioning
confidence: 99%
“…The assumption usually underlying this method is that depletion of natural resources is mostly triggered by deprivation and limited choices (Weaver et al ., ). Alternatives are segmented into three categories: the group that offers an alternative livelihood to replace the one being exploited, for example by promoting skill‐training as an alternative to illegal artisanal mining operations; the group that offers an alternative occupation to decrease the necessity to extract natural resources for income (Roe et al ., ); and those who promote an alternative method of extracting a resource that has a lesser impact than the original method, for example by promoting environmentally‐friendly mining to minimize the need to pollute the environment (DeWan et al ., ), thus encouraging skills‐training and oil palm or cocoa farming as a substitute for expanding illegal artisanal mining (Morgan‐Brown et al ., ).…”
Section: Artisanal Mining Alternative Livelihood Programmes (Alp) Anmentioning
confidence: 99%
“…Livelihood‐based approaches—also known as alternative livelihood (AL) projects—assume that providing alternative livelihood options will reduce natural resource exploitation (Brown, ). A systematic review of 106 AL projects found that only 22 met criteria for assessment, and only nine of these reported positive outcomes (Roe et al, ). Wright et al () argued that for AL interventions to succeed they need to provide a multifaceted substitute (e.g., in terms of labor inputs, cultural value, and economic rewards), to target the right users, and to scale to the wider region.…”
Section: Introductionmentioning
confidence: 99%